Improving the Efficiency of an Energy System with an Internal Combustion Engine Using a Solid Oxide Fuel Cell - Mytrofanov O.; Proskurin A.; Kong Wei (Problems of the Regional Energetics, 2025)
This paper explores the possibility of using a solid oxide fuel cell as part of an energy system with an internal combustion engine running on bioethanol, incorporating thermochemical waste gas heat recovery. The main goal of the research is to determine the efficiency of energy con-version in energy systems with deep waste gas heat recovery. To achieve this goal, the following tasks were set: based on experimental studies of a spark-ignition engine running on bioethanol, determine the parameters of the process for synthesizing gas through thermochemical conver-sion; theoretically investigate the efficiency of using a solid oxide fuel cell in combination with a bioethanol thermochemical conversion reactor. The most significant result is the determination of the volt-ampere characteristic of the solid oxide fuel cell and the identification of the poten-tial heat recovery capacity of the internal combustion engine exhaust gases through deep heat recovery. The significance of the obtained results lies in the theoretical and experimental valida-tion of efficient energy conversion of synthesis gas in a solid oxide fuel cell, achieving a high thermodynamic efficiency of the cell (0.95–0.75). The proposed energy system configuration, based on an internal combustion engine running on bioethanol with thermochemical waste heat recovery, allows for a 6.5% increase in the overall system power output. This contributes to re-duced fuel consumption and improved environmental performance. The research findings can be applied in the design and development of highly efficient energy systems with internal com-bustion engines for various applications.